Technology readiness of medical students and the association of technology readiness with specialty interest - MacNevin, Wyatt; Poon, Eric; Skinner, Thomas (Canadian Medical Education Journal, 2021)
Background: Technology readiness (TR) is a construct which characterizes an individual’s propensity to utilize new technology. Despite increased technology use in healthcare, limited data exists on medical student TR and the relation of TR with specialty interest. This study assesses the TR of 2nd year medical students and its association with specialty interest. Methods: Respondents completed a survey assessing their most preferred specialty, specialty interests, and technology readiness using a 5-point Likert scale. Using Chi-square analysis, we examined the relation between demographics, TR, and specialty interest. Results: This study obtained a 45.7% (n = 53/116) response rate demonstrating that 79.2% (n = 42/53) of students were “technology ready.” Male students were more likely to be technology ready (95.2%, n = 20/21, vs 68.8%, n = 22/32, p = 0.02) when compared to female students. Technology ready students were associated with being more interested in “Technology-Focused” specialties compared to students who were not technology ready (88.5%, n = 23/26 vs 70.4%, n = 19/27, p = 0.104). Conclusions: As a cohort, most medical students were technology ready. It is inconclusive if technology ready students are more likely to be interested in technology-focused specialties due to the limited sample size of this study, although with an increased sample size, an improved understanding on technology readiness and its potential impact on student specialty interest may be obtained. Furthermore, knowledge of TR may aid in developing targeted technology-based education programs and in improving remedial approaches for students who are less comfortable with new technology.